Safety and Pharmacokinetics of the Oral TYK2 Inhibitor PF‐06826647: A Phase I, Randomized, Double‐Blind, Placebo‐Controlled, Dose‐Escalation Study. Issue 2 (8th December 2020) - Singh, Ravi Shankar P.; Pradhan, Vivek; Roberts, Erika S.; Scaramozza, Matthew; Kieras, Elizabeth; Gale, Jeremy D.; Peeva, Elena; Vincent, Michael S.; Banerjee, Anindita; Fensome, Andrew; Dowty, Martin E.; Winkle, Peter; et al.
Abstract : Selective inhibition of tyrosine kinase 2 (TYK2) may offer therapeutic promise in inflammatory conditions, with its role in downstream pro‐inflammatory cytokine signaling. In this first‐in‐human study, we evaluated the safety, tolerability, and pharmacokinetics (PK) of a novel TYK2 inhibitor, PF‐06826647, in healthy participants. This phase I, randomized, double‐blind, placebo‐controlled, parallel‐group study included two treatment periods (single ascending dose (SAD) and multiple ascending dose (MAD)) in healthy participants and a cohort of healthy Japanese participants receiving 400 mg q.d. or placebo in the MAD period (NCT03210961). Participants were randomly assigned to PF‐06826647 or placebo (3:1). Participants received a single oral study drug dose of 3, 10, 30, 100, 200, 400, or 1, 600 mg (SAD period), then 30, 100, 400, or 1, 200 mg q.d. or 200 mg b.i.d. for 10 days (MAD period). Safety (adverse events (AEs), vital signs, and clinical laboratory parameters), tolerability, and PK were assessed. Overall, 69 participants were randomized to treatment, including six Japanese participants. No deaths, serious AEs, severe AEs, or AEs leading to dose reduction or temporary/permanent discontinuation were observed. All AEs were mild in severity. No clinically relevant laboratory abnormalities or changes in vital signs were detected. PF‐06826647 was rapidly absorbed with a median time to maximum plasma concentration of 2 hours in a fasted state, with modest accumulation (< 1.5‐fold) after multiple dosing and low urinary recovery. PF‐06826647 was well‐tolerated, with an acceptable safety profile for doses up to 1, 200 mg q.d. for 10 days, supporting further testing in patients.